2014
DOI: 10.1111/1748-8583.12040
|View full text |Cite
|
Sign up to set email alerts
|

Learning and development opportunities as a tool for the retention of volunteers: a motivational perspective

Abstract: The growing reliance on volunteers in Australia has heightened the need for non-profit organisations to retain these valuable resources. However, the current literature on volunteer retention is limited. One potential way volunteers can be retained is by providing learning and development opportunities (LDOs). This study investigates the relationship between volunteer perceptions of LDOs, their motivations for volunteering, and retention. Analyses revealed significant main effects for LDOs and volunteer motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 53 publications
1
68
0
Order By: Relevance
“…Interestingly, motivations for initial involvement have been shown to be a factor in longevity of involvement (Newton et al 2014), with people with certain motivations more likely to continue volunteering than others. For example, McDougle et al (2011) found that young people who were motivated to volunteer for social reasons were more likely to invest greater amounts of time in volunteering, compared to those who were motivated to learn new things or new skills.…”
Section: Motivationsmentioning
confidence: 99%
“…Interestingly, motivations for initial involvement have been shown to be a factor in longevity of involvement (Newton et al 2014), with people with certain motivations more likely to continue volunteering than others. For example, McDougle et al (2011) found that young people who were motivated to volunteer for social reasons were more likely to invest greater amounts of time in volunteering, compared to those who were motivated to learn new things or new skills.…”
Section: Motivationsmentioning
confidence: 99%
“…For instance, research shows that training facilitates the commitment and/or retention of volunteers of Australian rugby clubs (Cuskelly et al, 2006), Spanish social and ecological non-profit organizations (Hidalgo & Moreno, 2009), a wide range of Australian non-profits (Newton et al, 2014), bereavement volunteer programs in the US (Grossman & Furano, 1999), human and environmental organizations in the US (Tang, Morrow-Howell, & Hong, 2009), New Zealand sports volunteers (Allen & Shaw, 2009), Irish elderly volunteers helping youth to read (Devaney et al, 2015), volunteers of a UK-based religious non-profit organization involved in international relief and development efforts (Saksida et al, 2016), a range of US (Hager & Brudney, 2011;Jamison, 2003) and Spanish charities (Hidalgo & Moreno, 2009), and volunteer emergency response workers in the UK (Waikayi, Fearon, Morris, & McLaughlin, 2012).…”
Section: Ability-enhancing Hr Practicesmentioning
confidence: 99%
“…For instance, Newton et al (2014) found that volunteers with an understanding motive (the motivation to learn something new from volunteering) had higher levels of commitment when they were provided with learning and development opportunities, compared to volunteers with a weaker understanding motive. They also found that volunteers with strong career motives for volunteering reported significantly lower levels of intentions to stay; one explanation for this is that individuals with career motives, looking to gain skills, are likely to move to paid jobs once those skills are gained.…”
Section: Ability-enhancing Hr Practicesmentioning
confidence: 99%
See 2 more Smart Citations